PROFESSIONALISM IN TEACHING ENGLISH (Disampaikan pada Seminar “Menjadi Unggul dalam Penguasaan Bahasa Inggris di SMP – SMA” Sanata Dharma University, Yogyakarta, Juli 22 – 23, 2008) - Gustaman Saragih (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2010)
Students in Indonesia have already learned English since they were in Junior High School; in fact, some of them have studied English since they were in Elementary School but most of them are not able to speak English fluently even though they have graduated from Senior High Schools. This caused of Teachers taught English by focusing on grammar and using Indonesian as lingua franca when they were teaching. To solve the problem mentioned above, a new strategy is needed, the strategy which is appropriate to teaching English as a means of communication.Key words : English learning strategy, English as a means of communication